2017
DOI: 10.1371/journal.pone.0177480
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion on the servosphere: A potential tool for detecting inherent organismal movement patterns

Abstract: Tracking animal movements such as walking is an essential task for understanding how and why animals move in an environment and respond to external stimuli. Different methods that implemented image analysis and a data logger such as GPS have been used in laboratory experiments and in field studies, respectively. Recently, animal movement patterns without stimuli have attracted an increasing attention in search for common innate characteristics underlying all of their movements. However, it is difficult to trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
(40 reference statements)
0
23
0
Order By: Relevance
“…The mechanisms that generate biological Lévy walks can be classified into two types: mechanisms based on interaction with environments and those based on internal states. Although the former mechanisms are consistent with cases of Lévy walks observed in biological movements [14], the empirical evidence for intrinsically generated Lévy walks has been accumulating [18,19,20]. Theoretical studies on search efficiency have implicitly assumed that the movement patterns are caused by intrinsic mechanisms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The mechanisms that generate biological Lévy walks can be classified into two types: mechanisms based on interaction with environments and those based on internal states. Although the former mechanisms are consistent with cases of Lévy walks observed in biological movements [14], the empirical evidence for intrinsically generated Lévy walks has been accumulating [18,19,20]. Theoretical studies on search efficiency have implicitly assumed that the movement patterns are caused by intrinsic mechanisms.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies on spontaneous behavior have revealed that the temporal patterns of the intervals between consecutive turns or rest/movement without a stimulus often follow a power-law distribution [15,16,17], which is a hallmark of Lévy walks. In addition, the frequent correspondence of movement trajectories of some animal species in a featureless environment to Lévy walks has suggested that Lévy walks are generated intrinsically [18,19]. Moreover, the revelation by a recent study that Drosophila larvae exhibit Lévy walks even when their sensory neurons are blocked is strong evidence that Lévy walks are intrinsically generated, especially in the central pattern generators (CPGs) of the brain [20].…”
Section: Introductionmentioning
confidence: 99%
“…To measure the locomotor activity of A. venator , we used a treadmill system, ANTAM [18]. The ANTAM is developed from the omnidirectional treadmill mechanism system in which animal movements can be continuously recorded and compensated for in such a way that the animal is always located on the top of the sphere and experiences a virtual unbounded two-dimensional field [18]. Therefore, this system is able to measure the free walking trajectories of small animals such as insects [19].…”
Section: Methodsmentioning
confidence: 99%
“…The walking speed of A. venator is 26.60 ± 15.41 mm / sec (mean ± s.d., n = 133; unpublished), which is within the allowable range of the movement speed of the system used (for example, ANTAM can measure the walking speed of 55.2 ± 34.3 mm/sec (average ± s.d.) in the pill bug, Armadillidium vulgare [18]).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we created a theoretical framework to investigate random avoidance 200 behaviour in terms of Lévy walks, which have been observed widely in biological movements 201 [19][20][21][22][23][24][25]. We constructed a framework for prey-predator interactions based on the prey's 202 movements and the predator's prediction (figure 1) and calculated the predator's prediction rate, 203 the time length to reach the safety area and the prey's survival rate.…”
mentioning
confidence: 99%